Forest Installation Video for ICACA Art Exhibition 2024. - Auzani Zeda, Mohamed Kassim (2024)
The Forest Installation video presentation represents a research project funded by the grant titled 'Designing Projection-Based Audiovisual Installation for Gallery Spaces.' The project proposed an immersive installation that can be adapted for gallery or museum spaces with limited areas for showcasing.